Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Don't know if I'm simplifying wrong or if it is a simple mistake but I cannot get the answer of 4. Please help and include exact step by step details. Thank you.

$$f(x)=x^3 + 2x^2 + 1,\;\;\;c= -2$$

share|improve this question
3  
What do you mean by alternative formula? Could you be more specific? –  amWhy Jul 21 '13 at 1:44
    
Better yet, could you please edit to include what you've tried? That will help us to clear up any confusion. –  amWhy Jul 21 '13 at 1:52

3 Answers 3

Judging from one of your comments, you’re probably supposed to calculate

$$\begin{align*} \lim_{x\to-2}\frac{f(x)-f(-2)}{x-(-2)}&=\lim_{x\to-2}\frac{x^3+2x^2+1-\left((-2)^3+2(-2)^2+1\right)}{x+2}\\\\ &=\lim_{x\to-2}\frac{x^3+2x^2}{x+2}\\\\ &=\lim_{x\to-2}\frac{x^2(x+2)}{x+2}\;; \end{align*}$$

can you finish it from there?

share|improve this answer
    
Wow thank you so much. I completely see where I was messing it up. Thank you so much for the help, it is very greatly appreciated Brian. Thank you again. –  Nick Jul 21 '13 at 2:01
    
@Nick: You’re very welcome. –  Brian M. Scott Jul 21 '13 at 2:02

Using the alternative definition of the derivative, given what you posted in a comment, we'll start with the approximation of the derivative given by $\lim_{x \to -2}\dfrac{f(x) - f(c)}{x - c}$

\begin{align*}\require{cancel} \lim_{x \to -2} \dfrac{f(x) - f(c)}{x - c} &=\lim_{x\to -2} \dfrac{x^3 + 2x^2 + 1 - ((-2)^3 + 2(-2)^2 + 1)}{x - (-2)}\\ &=\lim_{x \to -2} \dfrac{x^3 + 2x^2 + 1 -(-8 + 2\cdot 4 + 1)}{x + 2}\\ &=\lim_{x \to -2} \dfrac{x^3 + 2x^2 + 1 - (1)}{x + 2}\\ &= \lim_{x \to -2} \dfrac{x^2({x + 2)}}{{x+2}}\\ &= \lim_{x \to -2} \dfrac{x^2\cancel{(x + 2)}}{\cancel{x+2}} \\ &= \lim_{x \to -2} x^2 = (-2)^2 = 4 \end{align*}

share|improve this answer
    
Thanks, for the editing @dfeuer! Looks much "prettier" to look at now :-) –  amWhy Jul 21 '13 at 3:42
    
You're welcome. Note that you need to \require{cancel} before you can use those nifty cancellations. –  dfeuer Jul 21 '13 at 3:58

If $f(x) = x^3 + 2x^2 + 1$, then $f'(x) = 3x^2 + 4x + 0$ from the power rule. Substituting $-2$ for $x$ we have that $f'(-2) = 3(-2)^2 + 4(-2) = 12 - 8 = 4$. On a side note, what value are you getting for $f'(-2)$?

share|improve this answer
    
I need it using the Alternative Form of the derivative, please and thank you. –  Nick Jul 21 '13 at 1:48
    
I am getting zero when using the alternative form –  Nick Jul 21 '13 at 1:49
1  
Would you mind telling us what the "alternative form" is? I don't know that this is standard nomenclature. –  Cameron Williams Jul 21 '13 at 1:49
    
f(x)-f(c)/x-c is what it shows in my calculus book –  Nick Jul 21 '13 at 1:53
    
That's not a derivative. That is the formula for the slope of a secant line - a related, but different concept. –  Cameron Williams Jul 21 '13 at 1:55

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.